2018
DOI: 10.1002/2211-5463.12521
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and biochemical characterization of the human dicarboxylate clamp TPR protein interaction network

Abstract: Dicarboxylate clamp tetratricopeptide repeat (dc TPR ) motif‐containing proteins are well‐known partners of the heat shock protein (Hsp) 70 and Hsp90 molecular chaperones. Together, they facilitate a variety of intracellular processes, including protein folding and maturation, protein targeting, and protein degradation. An extreme C‐terminal sequence, the EEVD motif, is identical in Hsp70 and Hsp90, and is indispensable for their interaction with dc TPR proteins. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Thus, a major goal in the proteostasis field is to understand when and where a particular complex between Hsp70 and its co-chaperones will assemble. This is a challenging problem because there are approximately 13 NEFs 9 , 44 JDPs 8 , and 35 TPR co-chaperone genes 28 and when these factors are combined with the 6 cytosolic Hsp70s 68 , an upper limit of >120,000 unique possible combinations are possible. While the true number of complexes is likely much lower than this value because of restrictions in subcellular localization and tissue-specific expression, studies have supported the broad idea that cells contain many Hsp70 complexes [69][70][71] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a major goal in the proteostasis field is to understand when and where a particular complex between Hsp70 and its co-chaperones will assemble. This is a challenging problem because there are approximately 13 NEFs 9 , 44 JDPs 8 , and 35 TPR co-chaperone genes 28 and when these factors are combined with the 6 cytosolic Hsp70s 68 , an upper limit of >120,000 unique possible combinations are possible. While the true number of complexes is likely much lower than this value because of restrictions in subcellular localization and tissue-specific expression, studies have supported the broad idea that cells contain many Hsp70 complexes [69][70][71] .…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the EEVD motifs and TPR co-chaperones have been extensively characterized [24][25][26][27] . Co-crystal structures of EEVD peptides bound to representative TPR domains have shown that a striking feature of this interaction is a "carboxylate clamp" in the TPR domain, involving lysine and arginine side chains, that coordinates the P1 aspartic acid and the EEVD's carboxy-terminus 28,29 . Biochemical studies have also shown that the identity of the P5 residue is also important, such that some co-chaperones have a strong preference for Hsp90's MEEVD over Hsp70's IEEVD [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Lys272, Lys352, Asn322, Glu273, and Lys329 were conserved throughout these proteins, out of which Lys272 and Lys352 are the two residues involved in the formation of the dicarboxylate clamp [161]. In another study, we have identified dcTPR interacting proteins having an acidic C-terminal domain similar to Hsp90/Hsp70 [162]. The development of ligands targeting the dcTPR domain for inhibition of Hsp90/cochaperone interaction is considered as an alternate strategy for drug development against these targets.…”
Section: Hsp90-tpr Co-chaperone Interaction Inhibitorsmentioning
confidence: 90%
“…, respectively, but to other protein containing a similar C-terminal sequence resulting in dicarboxylate clamp TPR interacting protein network. Functionally, these dcTPR interacting proteins can be classified as molecular chaperones, proteins involved in ubiquitin proteasomal system and proteins with miscellaneous functions as indicated by our recent study (Bernadotte et al 2018)…”
Section: Spatial Regulation Of Dctpr Protein Interaction Networkmentioning
confidence: 99%
“…The dcTPR proteins contain characteristic and conserved amino acid signature of K 5 -N 9 -N 40 -K 70 -R 74 which binds not only to the C-terminal peptide MEEVD and IEEVD of Hsp90 and Hsp70, respectively, but to other protein containing a similar C-terminal sequence resulting in dicarboxylate clamp TPR interacting protein network. Functionally, these dcTPR interacting proteins can be classified as molecular chaperones, proteins involved in ubiquitin proteasomal system and proteins with miscellaneous functions as indicated by our recent study(Bernadotte et al 2018)…”
mentioning
confidence: 99%